The Effect of Job Satisfaction, Transformational Leadership, and Job Stress on Organizational Commitment at PT Buana Jaya Lestari - Veronica Chua; Purnama Yanti Purba; Aprilia Chunitan (Institute of Computer Science (IOCS), 2021)
This study aims to examine and analyze the effect of job satisfaction, transformational leadership, and job stress on organizational commitment at PT Buana Jaya Lestari. The phenomenon of increasing employee turnover, inaccurate time in completing tasks which impact on not achieving company targets, meeting with leaders is not optimal, and lack of encouragement and direction from leaders towards employees is the background of this research. The research method is a quantitative approach, this type of research is descriptive quantitative and the nature of this research is descriptive explanatory. The data analysis method is multiple linear regression analysis. The sample collection technique is saturated sampling. The research sample was 66 employees. The results of the study are partially job satisfaction has a positive and significant effect on Organizational Commitment with tcount> ttable or 2.009> 1.999, Transformational Leadership has a positive and significant effect on Organizational Commitment with tcount> ttable or 5.716> 1.999, and Job Stress has a positive and significant effect on Commitment. Organizations with tcount> ttable or 2.465> 1.999. In addition, simultaneously Job Satisfaction, Transformational Leadership, and Job Stress have a positive and significant effect on Organizational Commitment with F count (28.710)> F table (2.75) and a significance probability of 0.000 <0.05.